2013
DOI: 10.3109/00365548.2013.855322
|View full text |Cite
|
Sign up to set email alerts
|

First insights into the molecular epidemiology of tuberculosis in Croatia during a three-year period, 2009 to 2011

Abstract: The most prevalent global lineage in Croatia is Euro-American (sub-lineages Haarlem, S, Cameroon, and Latin American-Mediterranean). The high clustering rate and high medium clustering size of 4.2 tuberculosis cases could indicate a possible failure in interrupting the transmission of infection and points to the need for improvements in national and local tuberculosis control activities. This is the first study describing the molecular epidemiology of tuberculosis in Croatia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…We found that in the setting of our hospital, which is located in a low-prevalence country, the sensitivity and specificity of the Xpert MTB/RIF were higher than the sensitivity and specificity of smear microscopy. These results are in line with all the studies conducted so far that have evaluated the performance of the Xpert MTB/RIF [2,21,22]. We next compared the semiquantitative result of the Xpert MTB/RIF with those of conventional microscopy using the international smear grading system [19] and found that the results of the Xpert MTB/RIF could be used as a predictor of smear result.…”
Section: Discussionsupporting
confidence: 82%
“…We found that in the setting of our hospital, which is located in a low-prevalence country, the sensitivity and specificity of the Xpert MTB/RIF were higher than the sensitivity and specificity of smear microscopy. These results are in line with all the studies conducted so far that have evaluated the performance of the Xpert MTB/RIF [2,21,22]. We next compared the semiquantitative result of the Xpert MTB/RIF with those of conventional microscopy using the international smear grading system [19] and found that the results of the Xpert MTB/RIF could be used as a predictor of smear result.…”
Section: Discussionsupporting
confidence: 82%
“…Studies were published between 2007 and 2014 and the clustering reported varied from 0% 37 to 62.8%. 38 In all studies, clustered isolates were defined as having identical strain types based on the MIRU-VNTR loci typed, with or without Spoligotyping. Seventeen studies included isolates from newly diagnosed TB cases, three studies reported including isolates from new and chronic cases of TB, and seven did not report this information.…”
Section: Resultsmentioning
confidence: 99%
“…Sensitivity analyses to examine the effect of excluding studies reporting 0% clustering, 37 only M. bovis cases, 39 studies using the ‘old 12’ MIRU loci, 39–44 and studies assessed as having a high risk of bias, 37 38 45–47 did not generally change the results. The proportion of culture-positive TB in the population remained insignificant but explained 2.6% of the between study variation when excluding 0% clustering (p=0.278 and adjusted R 2 =2.62).…”
Section: Resultsmentioning
confidence: 99%